(untitled) (Research, Society and Development, 2022)
The aim of this study was to assess the prevalence of awake bruxism (AB), temporomandibular disorders (TMD), quality of life (QoL), and their association with anxiety, depression, and stress levels, during COVID-19 lockdown. To this aim, 268 final-year dental students were asked about AB and TMD-related pain. QoL, anxiety and depression, and stress sensitivity were evaluated with the WHOQOL-bref instrument, the Hospital Anxiety and Depression Scale, and the Perceived Stress scale, respectively. Associations were tested by independent t-test, chi-square test, and simple regression analysis (α = 0.05). AB and TMD symptoms were reported by 54.8% and 64.2% of the volunteers, respectively, which presented worse quality of life (P < 0.05). Regression models showed that anxiety, depression, and stress predicted AB (P < 0.001) and QoL (P = 0.0001). Final-year dental students demonstrated high prevalence of self-reported AB and TMD, both of which correlated with lower QoL and were predicted by psychological factors.